A novel online assessment of pragmatic and core language skills: an attempt to tease apart language domains in children - Wilson, AC; Bishop, DVM (Cambridge University Press, 2021)
It remains unclear whether pragmatic language skills and core language skills (grammar and vocabulary) are distinct language domains. The present work aimed to tease apart these domains using a novel online assessment battery administered to almost 400 children aged 7 to 13 years. Confirmatory factor analysis indicated that pragmatic and core language domains could be measured separately, but that both domains were highly related (r = .79). However, zero-order correlations between pragmatic tests were quite small, indicating that task-specific skills played an important role in performance, and follow-up exploratory factor analysis suggested that pragmatics might be best understood as a family of skills rather than a domain. This means that these different pragmatic skills may have different cognitive underpinnings and also need to be assessed separately. However, our overall results supported the idea that pragmatic and core aspects of language are closely related during development, with one area scaffolding development in the other.